HUBUNGAN ANTARA POLA ASUH DENGAN STATUS GIZI PADA BALITA - Sa' Diyah, Halimatus; Sari, Dessy Lutfia; Nikmah, Anis Nikmatul (Universitas Kadiri, 2020)
ABSTRAK : The nutrional problem is esesentiallly a public health problem, and its causes are influenced by various factors related to one another. In addition to the physical needs of children also require guidance and affection from parents so that children are entitled to get best care because one of the factors that play an important role in the fulfillment of nutritional status of children is the pattern of care. The survey results on 8 parents (mother) who have toddlers, it were 62,5% of toddler have less nutriens because they not attention a nutrient of food and not care when a childs difficult for eat. Purpose to analyze the relationship of parenting pattern with nutritional status toddlers.Â Research method used is analytical korelasional with cross sectional design. Sampling technique that is sampling jenuh with amount of 47 sample. Data processing with rank sperman test with a significance level of (Î± = 0,05). Research results showed the majority of respondents (70,2%) have less parent and the majority of respondents (89,4%) have a good nutritional status. Spearman rank test results obtained Ï value = 0.001 <0.05, meaning there is a correlation between pattern of parent and nutritional status of toddlers.Â The better parenting parents increasingly normal nutritional status of children. Expected health workers provide counseling on the importance of appropriate parenting nutritional needs of children and doing the weigh regularly to monitor the nutritional status of children.Keywords: parenting, nutritional status